2007
DOI: 10.1111/j.1349-7006.2006.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific overexpression of OLFM4GW112/hGC−1 mRNA in colon, breast and lung cancer tissues detected using quantitative analysis

Abstract: Overexpression of the olfactomedin 4 (OLFM4GW112) gene was recently reported to inhibit various apoptotic pathways and promote proliferation of cancer cells, suggesting that OLFM4 might serve as a diagnostic marker for human cancers. Therefore, we examined cancer-specific OLFM4 overexpression. OLFM4 mRNA was highly expressed in cancerous tissues obtained from the colon, breast and lung. Positivity for OLFM4 mRNA, defined as the mean + + + + 2 SD in non-cancerous colon and breast tissues, was observed in 68 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 19 publications
2
72
3
Order By: Relevance
“…Although OLFM4 mRNA overexpression has been reported in CRC, 11 preoperative levels of olfactomedin 4 were increased in a small number of serum samples from CRC patients at stage I-III, indicating that serum olfactomedin 4 is unsuitable for early detection of CRC. The sensitivities of serum olfactomedin 4 at stage I-III was lower than those of CEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although OLFM4 mRNA overexpression has been reported in CRC, 11 preoperative levels of olfactomedin 4 were increased in a small number of serum samples from CRC patients at stage I-III, indicating that serum olfactomedin 4 is unsuitable for early detection of CRC. The sensitivities of serum olfactomedin 4 at stage I-III was lower than those of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast, immunohistochemical analysis has demonstrated that olfactomedin 4 down-regulation is found in late stage cases, and in patients with shorter survival of colon cancer. 12 The morphology and actin distribution of the HT-29 colon cancer cell line is altered by forced expression of olfactomedin 4.…”
mentioning
confidence: 97%
“…The fact that the olfactomedins have been identified only in multicellular organisms suggests that they play a role in cell-cell interaction and signalling. Olfactomedins are involved in normal development and are associated with several diseases including open-angle glaucoma and cancer [18][19][20][21][22]. OLFM1 and 3 are expressed mainly in the brain, OLFM2 in the pancreas and prostate, and OLFM4 in the bone marrow, small intestine, colon and prostate [15].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in OLFM1 [28] and silencing of OLFM1 resulted in increased apoptosis [29]. OLFM4 may have differing roles depending on the tissue, being antiapoptotic in gastric cancers [30] and growth promoting in pancreas and lung cancer cells [31,21]. Recently, OLFM4 in prostate cancer, suppressed growth and metastasis and exerted a negative impact on autophagy through interactions with Cathepsin D and stromal-derived factor 1 [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation